Strong fluorescence emission localized at a tapered silver-plated sub-wavelength pore. (17th October 2014) - Yang, Jin-Lei; Cao, Shuo-Hui; Liu, Qian; Zhao, Shuang; Zheng, Yu-Bin; Li, Yao-Qun
Abstract : Up to 200 times fluorescence enhancement was observed inside a tapered silver-plated sub-wavelength pore. Abstract : We observed up to 200 times fluorescence enhancement inside a tapered silver-plated sub-wavelength pore in comparison with the free space fluorescence. Fluorescence lifetime data was obtained to explore the strong fluorescence enhancement. The mechanism mainly arises from the silver film, the lateral dimensional shape, and size of the waveguide aperture.